PERBANDINGAN PERCEPATAN PENYEMBUHAN LUKA SIRKUMSISI MENGGUNAKAN ELEKTROCAUTER DENGAN MODERN KLEM DI WILAYAH KERJA PUSKESMAS PEMBANTU LIANG KABUPATEN MALUKU TENGAH 2021 - Thalib, Abdul; Hasan, Hulan (Pasapua Health Journal, 2022)
Introduction: Circumcision is the act of cutting or removing part or all of the skin covering the foreskin of the penis. Broadly speaking circumcision consists of several stages. First, an aseptic and antiseptic procedure, namely cleaning the penis and its surroundings using an antiseptic fluid with the aim of killing most of the bacteria, viruses and fungi around the operating field in order to minimize the risk of infection. The circumcision method is currently growing with a variety of circumcision techniques, previously the electocautery method with sutures has shifted to the modern clamp circumcision method without sutures. Several existing methods need to be evaluated so that people can find out the fundamental differences in each method. Methods: This study used an observational cross-sectional design, the research variables were measured at the same time during the study with the unpaired Mann Whitney test, a sample size of 18 respondents was carried out using the electrocautery circumcision technique for 9 people and the super ring clamp circumcision technique for 9 people. The level of wound healing was assessed from the inflammatory, proliferation and maturation phases using an observation sheet measuring instrument. Results: It was found that there was no significant comparison between electrocautery and modern clamps with a value of P=0.857 which means 0.05, so there is no comparison. In terms of the wound healing phase, the mean or average super ring clamps were higher with a difference in inflammation of 0.66, proliferation of 0.78 and maturation of 0.11. Conclusion: There is no significant difference between electrocautery technique and modern clamps in the circumcision process.